PENGARUH BUDAYA PERUSAHAAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DANA PENSIUN PERTAMINA DI JAKARTA - Sumarsid Sumarsid (CKI ON SPOT, 2017)
In this study the authors analyzed to determine the effect of corporate culture and motivation on employee performance improvement Pension Fund. From the analysis of multiple correlation coefficients obtained a correlation coefficient Culture Company X1 and X2 correlation coefficient Motivation to employee performance is 0950, thus the corporate culture and motivation strong and significant influence 0,000 <0.05 on the performance of the employee pension fund of Pertamina in Jakarta. Results of analysis of the coefficient of determination (R2) = 0.903 thus the corporate culture and motivation have contributed 90.3% to the Pension Fund employee performance in Jakarta, and the remaining 9.7% are influenced by other factors were not the authors carefully, including discipline , leadership, and quality of human resources. Based on the results of research by F test showed that the corporate culture and motivation simultaneously significant effect on employee performance improvement DPP (Pension Fund) in Jakarta, because sig. F count is 0000, meaning <5% (0.000 <0.005). Thus Ho rejected and Ha accepted. Based on testing with the t variable X1 is the corporate culture of -0.222 with t table is 1,701 and the value of the variable significant corporate culture X1 0.826> 5%, thereby to> tα then Ha (alternative hypothesis) refused and Ho (null hypothesis) is accepted , This means that the corporate culture is partially no significant effect on employee performance DPP (Pension Fund) in Jakarta. While the value of t count X2 motivation of 11 494 with the value t table is 1,701 and significant value for the variable X2 motivation 0000> 5%, thereby to <tα, That X2 motivation partially significant effect on employee performance Pension Fund in Jakarta.